Strengthening Cybersecurity Capacity Through the Implementation of Wazuh on the Server Infrastructure of LLDIKTI Region X: Peningkatan Kapasitas Keamanan Siber melalui Implementasi Wazuh pada Infrastruktur Server LLDIKTI Wilayah X - Karfindo; Hasan; Muhammad Diponegoro; Yusril Eka Mahendra; Mohammad Arifin (KPN Kopertis X, 2026)
Higher education service institutions increasingly depend on digital infrastructure, yet security monitoring of their servers is frequently absent, so incidents remain undetected until reported by outside parties. This community service programme addressed that gap at Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Region X, whose service applications run on Proxmox hypervisors hosting Ubuntu virtual machines without any centralised security monitoring. The objectives were to raise the technical understanding of the institution's IT personnel and to bring a working security monitoring system into operation on the partner's infrastructure. The programme combined technology diffusion, demonstration of technology, and mentoring. It was delivered at the STTIND Padang campus to fifteen IT managers attending on site, with the resource person presenting remotely by video conference, and continued afterwards as mentoring while the partner's own team carried out the installation. Nine structured modules covered the threat landscape, Wazuh architecture, agent deployment, log and alert analysis, file integrity monitoring, active response, vulnerability detection and security configuration assessment, an integrated attack scenario, and a thirty-day operational roadmap. Wazuh now operates on the partner's infrastructure in an all-in-one configuration with centralised log analysis, file integrity monitoring, vulnerability detection, configuration assessment, and automated response. The institution has moved from a reactive to a proactive security posture, sustained by a fifteen-minute daily operational checklist that the partner has adopted.